A Comparison Study Between CNN-Based Deformed Planning CT and CycleGAN-Based Synthetic CT Methods for Improving iCBCT Image Quality - Yang, Bo; Chang, Yankui; Liang, Yongguang; Wang, Zhiqun; Pei, Xi; Xu, Xie George; Qiu, Jie (Frontiers in Oncology, 2022)
Purpose: To compare two methods for improving the image quality of Varian Halcyon cone-beam CT (iCBCT) system through the deformed planning CT (dpCT) based on convolutional neural network (CNN) and the synthetic CT (sCT) generation based on the cycle-consistent generative adversarial network (CycleGAN). Methods: A total of 190 paired pelvic CT and iCBCT image datasets were included in the study, out of which, 150 were used for model training and the remaining 40 for model testing. For the registration network, we proposed a 3D multi-stage registration network (MSCnet) to deform CT images to agree with iCBCT images, and the contours from CT images were propagated to the corresponding iCBCT images through a deformation matrix. The overlap between the deformed contours (dpCT) and the fixed contours (iCBCT) was calculated for purposes of evaluating the registration accuracy. For the sCT generation, we trained the 2D CycleGAN using the deformation-registered CT-iCBCT slicers and generated the sCT with corresponding iCBCT image data. Then, on sCT images, physicians re-delineated the contours which were compared with contours of manually delineated iCBCT images. The organs for contour comparison included the bladder, spinal-cord, femoral-head-left, femoral-head-right and bone marrow. The Dice Similarity Coefficient (DSC) was used to evaluate the accuracy of registration and the accuracy of sCT generation. Results: The DSC values of the registration and sCT generation were found to be 0.769 and 0.884 for the bladder (P<0.05), 0.765 and 0.850 for the spinal-cord (P<0.05), 0.918 and 0.923 for the femoral-head-left (P>0.05), 0.916 and 0.921 for the femoral-head-right (P>0.05), and 0.878 and 0.916 for the bone-marrow (P<0.05), respectively. When the bladder volume difference in planning CT and iCBCT scans was over more than double, the accuracy of sCT generation was significantly better than that of registration (DSC of bladder: 0.859 vs. 0.596, P <0.05). Conclusion: The registration and sCT generation could both improve the iCBCT image quality effectively, and the sCT generation could achieve higher accuracy when the difference in planning CT and iCBCT was large.